Increased telestroke call burden after the extended thrombectomy window trials. (May 2023) - Almallouhi, Eyad; Debenham, Ellen; Grant, Cheryl; Spiotta, Alejandro M; Holmstedt, Christine A; Al Kasab, Sami
Introduction: Clinical trials have proven the efficacy of mechanical thrombectomy in stroke patients with large-vessel occlusion presenting within 24 hours of symptom onset. Extending the thrombectomy window to 24 hours resulted in a higher number of thrombectomies being performed. However, little is known about the impact of the extended thrombectomy window on the telestroke call burden. Methods: We used the prospectively maintained database of a telestroke network covering a large geographic area in the Southeast USA. We included patients presenting between January 2015 and December 2019. We compared the characteristics and outcomes between patients who presented before and after the publication of the extended window thrombectomy trials. Results: A total of 9041 patients presented with stroke-like symptoms during the study period. Of these, 4995 presented after February 2018. There was no difference in the patient demographics in both groups. However, patients in the post extended window group had a lower National Institute of Health Stroke Scale on presentation (3 vs. 4; p  < 0.001) and longer symptom-onset-to-door time (124 vs. 85 minutes; p  < 0.001). The number of consults per month nearly doubled (200 vs. 103; p  < 0.001) in the extended thrombectomy window era. Similarly, the number of mechanical thrombectomies performed per month increased from four to seven since extending the thrombectomy window ( p  < 0.001). Discussion: The number of telestroke consults nearly doubled after the publication of the extended thrombectomy window trials, with an increase in the number of thrombectomies performed. These findings have important operational implications for hospitals implementing telestroke call coverage.